Encyclopedia of Industrial Biotechnology 2010
DOI: 10.1002/9780470054581.eib170
|View full text |Cite
|
Sign up to set email alerts
|

Quality by Design (QbD), Biopharmaceutical Manufacture

Abstract: The main concepts of the quality by design (QbD) initiative and applicability to biomanufacturing are described. QbD can lead to a future where product quality will be assured by flexible, science‐based approaches. QbD is an umbrella of related concepts and approaches that include quality target product profiles, risk assessments, design spaces, control strategies using process analytical technology, continuous process improvement and others. We will also discuss the regulatory structure supporting the QbD ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…To gauge if adorbers and columns respond differently, three potential virus blocking impurities were studied in a resolution III design of experiment (DoE)‐based scheme (Table ). DoE approaches allow systematic evaluation of the impact of more than one parameter on unit operation performance . In the DoE, the impurities that were spiked into the feedstocks were CHO host cell proteins (HCP; 1 mg mL −1 ), fish genomic DNA (30 μg mL −1 ), a model for fragmented nucleic acid, and mouse genomic DNA (30 μg mL −1 ), a model for unfragmented nucleic acid (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To gauge if adorbers and columns respond differently, three potential virus blocking impurities were studied in a resolution III design of experiment (DoE)‐based scheme (Table ). DoE approaches allow systematic evaluation of the impact of more than one parameter on unit operation performance . In the DoE, the impurities that were spiked into the feedstocks were CHO host cell proteins (HCP; 1 mg mL −1 ), fish genomic DNA (30 μg mL −1 ), a model for fragmented nucleic acid, and mouse genomic DNA (30 μg mL −1 ), a model for unfragmented nucleic acid (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Model impurities were either purchased (Herring DNA for low molecular weight DNA, Sigma cat number D3159, St Louis, MO) or produced in house (full‐length Mouse genomic DNA, prepared by standard molecular biology techniques as described in Norling et al; SP2/0 host cell proteins, extracted from a filtered, homogenized cell pellet lysate, followed by high salt anion exchange chromatography to remove nucleic acids). High (+1) and low (−1) ranges of model impurities (Table ) were chosen based on extreme case values cited in industrial applications (data not shown) and the scientific literature . For DoE studies, the impurities were spiked into the feedstocks for each resin or membrane type based on a resolution III design…”
Section: Methodsmentioning
confidence: 99%
“…The ICH Guidance for Industry Q8(R2) Pharmaceutical Development Quality by Design (QbD) annex 17 calls upon biotechnology and pharmaceutical manufacturers to identify critical process parameter ranges where consistently high-quality product is produced. 18,19 However, varying all of the potential cell culture factors would result in a colossal and costprohibitive study, even if performed in parallel cultures. Also, it is likely that not all possible bioreactor or cell culture parameters will impact CQAs, especially when maintained within typical commercial manufacturing ranges.…”
Section: Introductionmentioning
confidence: 99%